Vitamin D Induces Differential Effects on Inflammatory Responses During Bacterial and/or Viral Stimulation of Human Peripheral Blood Mononuclear Cells - Anderson, Jeremy; Do, Lien Anh Ha; Toh, Zheng Quan; Hoe, Edwin; Reitsma, Andrea; Mulholland, Kim; Licciardi, Paul V. (Frontiers in Immunology, 2020)
Streptococcus pneumoniae (pneumococcus) and respiratory syncytial virus (RSV) are the leading causes of respiratory infections amongst children <5 years of age. Co-infection with these pathogens is common during early life and often associated with increased disease severity. Epidemiological studies have shown that low levels of Vitamin D3 (VitD3) are associated with increased susceptibility to respiratory pathogens. However, the role of VitD3 in the context of pneumococcal and RSV exposure are poorly understood. We found that VitD3 significantly reduced Th17 cell expression and IL-17A and IL-22 secretion in peripheral blood mononuclear cells (PBMCs) when stimulated with a pneumococcal whole cell antigen (WCA). Levels of IFN-γ were also decreased whilst IL-10 and IL-1β were increased. Effects of VitD3 on innate responses following RSV stimulation was limited, only reducing IL-6. VitD3 also reduced the number of TLR2+CD14+ monocytes, whilst increasing TLR7+CD14+ monocytes and TLR4+CD56+ NK cells. In WCA-stimulated PBMCs, VitD3 increased IL-1β levels but reduced TLR2+CD14+ monocytes. For pneumococcal WCA-RSV co-stimulation, VitD3 only had a limited effect, mainly through increased IL-1β and RANTES as well as TLR4+CD56+ NK cells. Our results suggest that VitD3 can modulate the inflammatory response to pneumococci but has limited effects during viral or bacterial-viral exposure. This is the first study to examine the effects of VitD3 in the context of pneumococcal-RSV co-stimulation, with important implications on the potential role of VitD3 in the control of excessive inflammatory responses during pneumococcal and RSV infections.